PENGARUH METODE KOAGULASI, SEDIMENTASI DAN VARIASI FILTRASI TERHADAP PENURUNAN KADAR TSS, COD DAN WARNA PADA LIMBAH CAIR BATIK - Rahmah, Rahmah; Mulasari, Surahma Asti (CHEMICA: Jurnal Teknik Kimia, 2015)
Batik  industry  in  Indonesia  increased,  so  that  the  impact  result  from the production  process  in  the  form  of  wastewater  is  increasing.  Wastewater disposal after staining and   washing    process    without    processing    will    improve environmental contamination such as TSS, COD and color levels. The problems of batik wastewater contamination can be resolved by treatment of wastewater in chemistry and physics. One way batik wastewater treatment are coagulation, sedimentation and filtration. Filtration media are used as filter media is activated charcoal, quartz sand and zeolite. The purpose  of  this  research  to  determine  the  effect  of  coagulation,  sedimentation  and filtration variation method to decreased levels of TSS, COD and color in the wastewater of batik. The type of this research was a true experiment with pre-test post-test group design.  Samples  of  this  research  were  batik  wastewater  with  levels  of  TSS,  COD  and color  are  818  mg/  l,  1133,57  mg/  l  and  100  TCU.  Data analyzed using one-way ANOVA. The  result  after  treatment  of  coagulation,  sedimentation  and  filtration  variety occurs  decreased  levels  of  TSS,  COD  and  color  on  filtration  variation  of  activated charcoal  and  quartz  sand,  respectively  for  99,8%,  99,49%  and  99,6%,  variation  of  the zeolite filtration and activated charcoal was, 99,6%, 92,31% and 99,5%, and  variations in zeolite filtration and quartz sand was 99,7%, 89,92% and 99,3%. Based on the statistical test using ANOVA test on the TSS levels were obtained p= 0,190, while the COD were obtained value of p= 0,008 and the value of color was p= 0,017. The methods of coagulation, sedimentation and filtration variation using activated charcoal, quartz sand and zeolite can reduce TSS, COD and color levels.  There is no difference between the   variation of filtration to decrease levels of TSS, while there is a difference between the variation filtration to decreased levels of effluent COD and color Batik.